A case of naturally occurring anti-Dia antibody in a young man - Salfarina Iberahim; Noor Haslina Mohd Noor; Mohd Nazri Hassan; Rosnah Bahar; Shafini Mohdmed Yusoff; Marini Ramli; Wan Suriana Wan Abdul Rahman; Zefarina Zulkafli; Marne Abdullah; Ho Sook Fong; Tengku Muzaffar Tengku Mohamed Shihabudin; Hisham Atan Edinur; et al. (Asian Journal of Transfusion Science, 2022)
The Diego (Di) blood group system comprises 22 antigens located on the band 3 protein, most of which are low-prevalence antigens. The majority of antibodies to Diego system antigens were of clinically insignificant; however anti-Dia, -Dib, -Wra, -ELO and-DISK may cause hemolytic disease of the fetus and newborn (HDFN) and transfusion reaction. We reported a case of naturally occurring of anti-Dia in a young man who presented to our hospital for wound debridement of fingers injury. His serological results were suggestive of anti-Dia antibody, and his molecular blood group showed he has Di (a-b+) antigen. Anti-Dia may be clinically significant. It can cause mild-to-severe HDFN, but there are only infrequent reports of it being clearly implicated in a hemolytic transfusion reaction. We suggest the need for reagent red blood cell panels to include Dia antigen-positive cells in antibody identification tests for our populations.